Analisis Struktur Lagu My Heart Ciptaan Melly Goeslaw - Angga Saputra; Jagar Lumbantoruan (SENDRATASIK UNP, 2021)
This study is about Melly Goeslaw's My Heart Song Structure Analysis related to motives, phrases, periods, and forms. This research includes qualitative research with content analysis that is symmetrical, objectivity, and generalization. This research data was collected from the activities of Library Study, Observation, and Transcription / Labor Work.  The result of the study is that the song My Heart created by Melly Goeslaw formed by motifs, phrases, periods to produce form. Rhythmic and melodic basic motifs coupled with development techniques. Overall found as many as 23 motifs namely m, m1, m2, n, n1, n2, o, o1, o2, p, p1, p2, k, k1, k2, l, l1, q, q1, r, r1, r2, r3 with 16 phrases consisting of antecedents and consequents i.e. a, a1, a2, b, b1, b2, c (2x reps), c1, c2, d (1x reps) , d1, d2 and d. The song also consists of 4 forms namely A, B, C, D through the processing of motifs and phrases, in the phrase created the form of the song into A, A', B, B', C, B, D, D' with the period arrangement A (a, b), A' (a1, b1), B (c, d), B' (c, d1), C (a2, b2), B (c, d), D (c1, d2) and D' (c2 , d3). The song also has kadens namely half cadence, the picardie third, the imperfect authentic cadence and the perfect authentic cadence.